Nonstandard work schedules in 29 European countries, 2005–15: differences by education, gender, and parental status - Pablo Gracia; Wen Jui-Han; Jianghong Li (Monthly Labor Review, 2021)
Data from the European Working Conditions Surveys from 2005, 2010, and 2015 for 29 European countries show that the prevalence of nonstandard work schedules (evenings, nights, weekends, and rotating shifts) differs markedly across European regions with different public policies. Working nonstandard schedules also differs by education, gender, and parental status across Europe.
Keywords: 330; labor law; sampling; child care; employment; family issues; recession; survey methods; men; women; expansions; economic and social statistics; Germany; Poland; Netherlands; Denmark; Sweden; Norway; Czech Republic; France; Slovakia; Belgium; Europe; United Kingdom; Italy